Hubungan Jumlah Pemberian Hijauan dan Jumlah Pemberian Air Minum Terhadap Umur Pertama Beranak Sapi PO - Kunaifi Wicaksana; Dani Nur Arifi (Wahana Peternakan, 2021)
ABSTRACT This study aims to analyze the relationship between the amount of forage and the amount of drinking water given to the age at first birth so that it can be used as material for improvement in management of PO cattle breeding. The research method was in the form of a survey, the data variables were the amount of forage, the amount of drinking water, and the first calving age and the data analysis was descriptive, regression and correlation. The results of the study, the first calving age 3.36 Â± 0.50 years was classified as slower. The amount of forage and the amount of drinking water had a very significant effect and was negatively associated with the calving first age. The closeness level of the amount of forage and the amount of drinking water given to the age at first birth was classified as moderate. Based on the results of the study, it can be concluded that, the first calving age is 3.36 Â± 0.50. The amount of forage and the amount of drinking water had a very significant effect and was negatively associated with the first calving age. The level of relationship between the amount of forage and the amount of drinking water for the first calving age is moderate. Key words: The amount of drinking water, the amount of forage, the first calving age, PO cattle. Â